PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abdullah Abdullah (AkMen JURNAL ILMIAH, 2015)
Effect of Current Ratio, Debt to Equity Ratio, Return On Equity, and Working Capital Turnover on stock price in Food and Beverages listed in the Indonesia Stock Exchange Year 2012 to 2014. This study aims to determine the effect the Current Ratio, Debt to Equity Ratio, Return on Equity, and Working Capital Turnover partially, or simultaneously to the stock price in Food and Beverages listed in the Indonesia Stock Exchange Year 2012 to 2014. The population in this study is of Manufacturing subsector food and beverages listed on the Indonesian stock exchange by 15 companies. Samples were ten (10) companies were selected based on criteria, namely: Food and Beverage Company listed on the Indonesia Stock Exchange Year 2012 to 2014; Publish audited financial statements; Has the advantage (profit); and never share cash dividend during the observation period. These results indicate that the Current Ratio (X1) Debt to Equity Ratio (X2) and Working Capital Turnover (X4) partially no significant effect. While Return on Equity (X3) positive and significant impact on stock prices in Food and Beverages listed in the Indonesia Stock Exchange Year 2012 to 2014. Simultaneously Current Ratio (X1), Debt to Equity Ratio (X2), Return on Equity (X3), and the Working Capital Turnover (X4) Positive and significant effect on stock price in Food and Beverages listed in the Indonesia Stock Exchange in 2012 -2014. The dominant influential variable is Return On Equity (X3).